Cash transfers for HIV prevention: what do young women spend it on? Mixed methods findings from HPTN 068 - Catherine MacPhail; Nomhle Khoza; Amanda Selin; Aimée Julien; Rhian Twine; Ryan G. Wagner; Xavier Goméz-Olivé; Kathy Kahn; Jing Wang; Audrey Pettifor (BMC, 2017)
Abstract Background Social grants have been found to have an impact on health and wellbeing in multiple settings. Who receives the grant, however, has been the subject of discussion with regards to how the money is spent and who benefits from the grant. Methods Using survey data from 1214 young women who were in the intervention arm and completed at least one annual visit in the HPTN 068 trial, and qualitative interview data from a subset of 38 participants, we examined spending of a cash transfer provided to young women conditioned on school attendance. Results We found that spending was largely determined and controlled by young women themselves and that the cash transfer was predominately spent on toiletries, clothing and school supplies. In interview data, young women discussed the significant role of cash transfers for adolescent identity, specifically with regard to independence from family and status within the peer network. There were almost no negative consequences from receiving the cash transfer. Conclusions We established that providing adolescents access to cash was not reported to be associated with social harms or negative consequences. Rather, spending of the cash facilitated appropriate adolescent developmental behaviours. The findings are encouraging at a time in which there is global interest in addressing the structural drivers of HIV risk, such as poverty, for young women. Trial registration Clinicaltrials.gov NCT01233531 (1 Nov 2010). First participant enrolled 5 March 2011.